1962
DOI: 10.2136/sssaj1962.03615995002600060018x
|View full text |Cite
|
Sign up to set email alerts
|

Factors Responsible for Poor Response of Corn and Grain Sorghum to Phosphorus Fertilization: II. Lime and P Placement Effects on P‐Zn Relations

Abstract: Soil factors controlling Zn concentration in the corn plant are very complex, including among others a beneficial action of applied N and a detrimental action of P or lime inherently present or added to the soil. It is apparent that Zn deficiency is likely to be aggravated or created by row application at low rates or heavier mixed applications of readily available P fertilizer. The problem is greatest on soils that are calcareous and especially on those of high inherent P supply where plant Zn concentration a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
10
0
1

Year Published

1972
1972
2009
2009

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(18 citation statements)
references
References 0 publications
7
10
0
1
Order By: Relevance
“…A possibilidade de que o Ρ parece bloquear a absorção de Zn e que a interação entre os dois nutrientes ocorre na superfície da raiz ou dentro delas, foi defendida por LANGIN et al, (1962). STUKENHOLTZ et al, (1966) SHARMA et al, (1968 e PAULSEN e ROTIMI (1968) mostraram que o principal efeito do fosfato foi uma inibição na translocação do Zn da raiz à parte aérea da planta.…”
Section: Introductionunclassified
“…A possibilidade de que o Ρ parece bloquear a absorção de Zn e que a interação entre os dois nutrientes ocorre na superfície da raiz ou dentro delas, foi defendida por LANGIN et al, (1962). STUKENHOLTZ et al, (1966) SHARMA et al, (1968 e PAULSEN e ROTIMI (1968) mostraram que o principal efeito do fosfato foi uma inibição na translocação do Zn da raiz à parte aérea da planta.…”
Section: Introductionunclassified
“…Loneragan et al (1979) reported Zn-deficiencylike symptoms in subterranean clover (Trzfolium subterraneum L.) following P applications. Zinc deficiency in corn is often aggravated by P fertilization, especially on calcareous soils (Langin et al, 1962). Vesicular-arbuscular mycorrhizae inoculation can sometimes increase Zn uptake and eliminate Zn deficiency symptoms (Bowen et al, 1974;Neilsen and Jensen, 1983).…”
mentioning
confidence: 99%
“…It is also well established that P availability is reduced as soil acidity increases. On the other hand, Langin et al (1962) and Shukla and Morris (1967) observed that application of limestone or phosphorus, or both, can lead to reduced zinc (Zn) concentration in corn. Liming is also known to reduce the availability of boron (B) (Berger 1949 10-cm soil depth, were maintained at I2.l atd 7.1 C, respectively, during the 1st week, and were increased gradually on a weekly basis to 2l.O and 17.6 C by the 8th week.…”
Section: Introductionmentioning
confidence: 99%